The assassin bug subfamily Harpactorinae (Hemiptera: Reduviidae) from Vietnam: an annotated checklist of species - Lam, Truong Xuan; Cai, Wanzhi; Tomokuni, Masaaki; Ishikawa, Tadashi (Zootaxa, 2015)
A checklist of all known Vietnamese species of the assassin bug subfamily Harpactorinae (Hemiptera: Heteroptera: Reduviidae) is presented with distributional and taxonomic notes. Sixty-five species in 35 genera of the subfamily are recognized in Vietnam. Eleven genera and 32 species are reported herein for the first time from this country. Newly recorded genera are Henricohahnia Breddin, 1900, Kalonotocoris Miller, 1941, Lingnania China, 1940, Lopodytes Stål, 1853, Macracanthopsis Reuter, 1881, Sclomina Stål, 1861, Serendiba Distant, 1906, Serendus Hsiao, 1979, Vesbius Stål, 1866, Villanovanus Distant, 1904, and Yolinus Amyot & Serville, 1843. New record species are Biasticus confusus Hsiao, 1979, B. flavinotus (Matsumura, 1913), Cosmolestes annulipes Distant, 1879, C. pulcher Hsiao, 1979, Cydnocoris fasciatus Reuter, 1881, C. gilvus (Burmeister, 1838), Endochus nigricornis Stål, 1859, Henricohahnia vittata Miller, 1954, Isyndus heros (Fabricius, 1803), I. pilosipes Reuter, 1881, Kalonotocoris curvipes Miller, 1941, Lingnania braconiformis China, 1940, Lopodytes spectabilis Miller, 1941, Macracanthopsis nodipes Reuter, 1881, Sclomina erinacea Stål, 1861, Serendiba nigrospina Hsiao, 1979, S. staliana (Horváth, 1879), Serendus geniculatus Hsiao, 1979, Sphedanolestes annulipes Distant, 1903, S. gularis Hsiao, 1979, S. impressicollis (Stål, 1861), S. pubinotus Reuter, 1881, S. trichrous Stål, 1874, S. xiongi Cai & Cai, 2004, Sycanus croceus Hsiao, 1979, Velinus annulatus Distant, 1879, V. malayus (Stål, 1863), V. rufiventris Hsiao, 1979, Vesbius purpureus (Thunberg, 1784), V. sanguinosus Stål, 1874, Villanovanus nigrorufus Hsiao, 1979, and Yolinus albopustulatus China, 1940. All the species are examined with Vietnamese materials except for Agriosphodrus dohrni (Signoret, 1862), Cydnocoris russatus Stål, 1867, and Sycanus atrocoeruleus Signoret, 1862.